Effects of the Interleukin-6 Receptor Blocker Sarilumab on Metabolic Activity and Differentiation Capacity of Primary Human Osteoblasts - Annett Klinder; Janine Waletzko-Hellwig; Marie-Luise Sellin; Anika Seyfarth-Sehlke; Markus Wolfien; Franziska Prehn; Rainer Bader; Anika Jonitz-Heincke (Pharmaceutics, 2022)
Interleukin (IL-) 6 is a key factor in the inflammatory processes of rheumatoid arthritis. Several biologic agents target the IL-6 signaling pathway, including sarilumab, a monoclonal antibody that blocks the IL-6 receptor and inhibits IL-6-mediated cis- and trans-signaling. A careful analysis of the IL-6 signaling blockade should consider not only inflammatory processes but also the regenerative functions of IL-6. The purpose of this study was to investigate whether inhibition of the IL-6 receptors affects differentiation of human primary osteoblasts (hOB). The effects of sarilumab on viability and the differentiation capacity in unstimulated osteoblasts as well as after stimulation with various IL-6 and sIL6-R concentrations were determined. Sarilumab treatment alone did not affect the differentiation or induction of inflammatory processes in hOB. However, the significant induction of alkaline phosphatase activity which was observed after exogenous IL-6/sIL-6R costimulation at the highest concentrations was reduced back to baseline levels by the addition of sarilumab. The IL-6 receptor blockade also decreased gene expression of mediators required for osteogenesis and bone matrix maintenance. Our results demonstrate that concomitant administration of the IL-6 receptor blocker sarilumab can inhibit IL-6/sIL-6R-induced osteogenic differentiation.